MOLECULAR CHARACTERIZATION OF FECAL MICROBIOTA OF HEALTHY CHINESE TOBACCO SMOKER SUBJECTS IN SHAANXI PROVINCE, XI'AN CHINA - Ishaq, Hafiz Muhammad; Shahzad, Muhammad; Wu, Xiaokang; Ma, Chaofeng; Xu, Jiru (Journal of Ayub Medical College Abbottabad, 2017)
Background: Tobacco Smoking, most commonly, can cause the diseases affecting the lungs and heart. Human gut microbiota plays a key role to decide the health status of the host. Current study aimed to characterize the gut microbiota of healthy Chinese tobacco smokers and to study the alteration in diversity and similarity of gut microbiota, with comparison of healthy non-smokers. Methods: Fecal samples were collected from fourteen healthy tobacco smokers and six from healthy non-smoker individuals. PCR-denaturing gradient gel electrophoresis, with universal primers focusing V3 region of the 16S rRNA gene, was done to characterize the overall gut microbial composition of healthy tobacco smokers in comparison with healthy non-smoker subjects and some strongly dominant gel bands were excised for sequencing. Real time PCR was also performed to evaluate the copy numbers of some dominant bacteria of intestinal flora. Results: The results indicated that gut microbial diversity in tobacco smoker group was lower than non-smoker controls. Furthermore, similarity index comparison also indicated that it was lower in inter-group than intra-group, which showed that gut microbial composition was changed in tobacco smoker group. Sequencing results also indicated a change in bacterial composition between both groups. We also observed that in tobacco smoker group, there was a significant reduction in Bifidobacterium and non-significant increase in Bacteroides vulgatus, while non-significant decrease in Lactobacillus and clostridium leptum sub group, respectively. Conclusion: It can be concluded that in healthy Chinese tobacco smoker group, there is a notable alteration in the molecular characterization of gut microbiota. Keywords: Tobacco smokers; Gut microbiota; Characterization; DGGE